Penyelesaian Permasalahan Menggunakan Konsep SMART CITY di Kota Bandung - Syahrul Ramadhan (Ruang, 2019)
The smart city application in cities of Indonesia is still a little bit because the concept of smart city is fairly new in Indonesia, or maybe because there are not many examples that can be emulated by other cities in Indonesia. This paper explains about smart city, urban problems in Indonesia and the application of the smart city concept in Bandung to solve urban problems in the city of Bandung. The research method used is a literature study. Bandung city is one of the cities that has successfully implemented the smart city concept, especially in the fields of green open space (parks) in transportation and public services.